Трансгенерація історичної травми в середовищі росіян-старообрядців (на прикладі харківської общини старообрядців-безпоповців Поморської згоди) - Арзуманова, Т. В. (НТУ "ХПІ", 2014)
Досліджено вплив травмуючих історичних подій, пережитих родинами старообрядців, на їх поведінку, життєві стратегії та адаптивні практики (зокрема, виживання за умов репресій). Зроблено висновок про наявність посттравматичного синдрому в середовищі старообрядців, який передається наступним поколінням. Його симптомами виступають страх, підозрілість, недовіра до іновірців, невпевненість у майбутньому, тривога та очікування можливих переслідувань, депресії, відчуття горя і приниження.

The effect of traumatic historical events that have been experienced by the families of Old Believers is analyzed. The influence of historical trauma on the Old – Believers behavior, strategies and adaptive life practice (their surviving during the centuries of repression) was investigated. The conclusion about the posttraumatic syndrome in the Old Believers society was made. The posttraumatic syndrome has the transgenerational transmission. Its symptoms are the fear, suspicion, and mistrust of people of other faiths, uncertainty about the future, anxiety and expectation of the persecution, depression, feelings of grief and humiliation.
Transgeneration historical wound among the Russian old believers (on the example of Kharkiv community of believers-the bespopovtsy Pomorsky consent)
Keywords: історична пам'ять; історична травма; трансгенерація; посттравматичний синдром; старообрядці; historical memory; historical trauma; transgeneration; Old Believers; posttraumatic syndrome